Water hyacinth as a biomass: A review. (20th December 2020) - Gaurav, Gajendra Kumar; Mehmood, Tariq; Cheng, Liu; Klemeš, Jiří Jaromír; Shrivastava, Devesh Kumar
Abstract: Worldwide available, attractive, and invasive biomass as water hyacinth and its characteristic has been discussed in this review. Water hyacinth biomass, as well as its production, characterization and applications, are specifically analysed. The basic principles for the conversion of biomass into biochar via physiochemical processes as well as their usability with catalyst are also elaborated which enhance their quality of products. Water hyacinth has been gained much attention in biochar production, biomethane, biohydrogen, biogas, and utilisation in case of wastewater treatment. Even more focused consideration is still needed to develop integrated decentralized water systems and production of the most valuable and qualitative products like biochar used in power generation. They can be used for various purposes in soil amendment, pollution abatement, carbon dioxide sequestration, CO2 capture etc. Economic analysis should be done for the profitability of the process. Graphical abstract: Image 1 Highlights: Basic mechanism and metabolism of WH has been discussed. An overview on the WH biomass in biochar production has been accomplished and also described economic analysis in brief. Structure, distribution, mathematical models has been described elaborately. Challenges and future prospects of WH biomass have been illustrated.